Environmental benefits of incorporating palm oil fuel ash in cement concrete and cement mortar - Jokhio, Gul A.; Hamada, Hussein M.; Humada, Ali M.; Gul, Yasmeen; Abu-Tair, Abid (EDP Sciences, 2020)
Palm oil fuel ash (POFA) is a by-product waste material from palm oil with many economic and environmental benefits. A lack of enough information on the advantages of POFA in the concrete production in various proportions was the main cause to carry out this work. This paper shows advantages of POFA as a partial replacement of cement in concrete production, especially cement mortar. The data collection has been done from the literature review related to the use of POFA as partial cement replacement in the production of cement concrete and mortar. Therefore, this paper can potentially become a guide for researchers and manufacturers to use POFA in various proportions to replace the ordinary Portland cement (OPC) in cement concrete and mortar. The positive and negative impact resulting from this material has been discussed carefully. This study recommends that researchers and academics should perform more experimental works in order to illustrate the desired benefits from POFA as cement replacement, thus mitigate the adverse environmental impacts of cement.